Assessing the Environmental Kuznets Curve and Carbon Tax Implementation Challenges in Indonesia - Leasiwal, Teddy Christianto; Husein, Hartina (International Journal of Energy Economics and Policy, 2025)
This study examines the Environmental Kuznets Curve (EKC) hypothesis in Indonesia and investigates the multifaceted challenges of carbon tax implementation within the country’s unique development context. Utilizing a mixed-methods approach, the quantitative analysis employs panel data from 1990 to 2024 and advanced econometric techniques to empirically confirm the inverted U-shaped EKC, revealing that Indonesia remains on the ascending phase where economic growth increases greenhouse gas (GHG) emissions. Control variables such as energy consumption, industrialization, and urbanization further contribute to emissions growth. The qualitative analysis, based on policy document reviews and stakeholder interviews, identifies key barriers to effective carbon tax enforcement, including regulatory fragmentation, industrial lobbying, technical readiness deficits, equity concerns, and political communication challenges. The novelty of this research lies in explicitly linking Indonesia’s position on the EKC ascending slope to the implementation challenges of carbon tax policy, providing a comprehensive and contextualized understanding beyond prior studies. The findings stress the imperative for gradual, integrated carbon tax policies paired with transparent revenue recycling mechanisms and effective communication strategies to overcome resistance and drive sustainable economic transition. This integrated approach offers valuable insights and actionable recommendations that align policy design with Indonesia’s developmental trajectory and climate commitments.